Distribution of insecticide resistance and molecular mechanisms involved in the West Nile vector Culex pipiens in Morocco. Issue 3 (31st October 2020) - Arich, Soukaina; Assaid, Najlaa; Taki, Hassan; Weill, Mylène; Labbé, Pierrick; Sarih, M'hammed
Abstract: BACKGROUND: Mosquitoes of the Culex pipiens complex are the vectors of several arboviruses and are thus subjected to insecticide control worldwide. However, overuse of insecticides selects for resistance. While assessing the resistance status of the vectors is required for effective and sustainable disease control, resistance has so far only been sparsely studied in Morocco. In this study, we establish a first countrywide assessment of the levels of resistance to various insecticides and the potential responsible mechanisms involved. Cx. pipiens larvae were collected from natural populations of five regions of Morocco, and their taxonomic status was determined (molecular forms). The level of their susceptibility to insecticides was assessed by single‐diagnostic‐dose bioassays. Molecular identification of known resistance alleles was investigated to determine the frequency of target‐site mutations. RESULTS: This study confirms that Moroccan populations are an interbreeding mix of pipiens and molestus forms, with large gene flow for the resistance alleles. We also found that Cx. pipiens mosquitoes are resistant to all insecticide families, all over Morocco: resistance is high for insecticides used in mosquito control, but also present for other pesticides. Resistance alleles are similarly more frequent for mosquito control insecticides. However, their distribution is heterogeneous in the five regions, with significant genetic differentiation between populations, revealing the crucial role of local insecticide treatment practices. CONCLUSION: This study provides reference countrywide data that highlight the need for further research to refine the distribution of resistance in Morocco and to understand the role of agriculture/urban residuals in its spread. © 2020 Society of Chemical Industry Abstract : This study confirms that Moroccan populations of Culex pipiens have a large gene flow for resistance alleles. They are resistant to all insecticide families, all over Morocco.